Przygotowanie dalsze i bliższe do małżeństwa po Dekrecie ogólnym Konferencji Episkopatu Polski z 2019 r. - Dullak, Kazimierz (Ius Matrimoniale, 2020)
Getting married in the Catholic Church should be preceded by preparation divided into three stages: further, closer and direct. In Poland, since June 1st , 2021, an episcopal document is in force, specifying in particular canonical and pastoral talks with the engaged couples. The earlier stages of marriage formation have been discussed in scattered legal acts. These documents have the scope of the universal Church and the others are in force in Poland. This study summarizes the regulations that are in force in Poland, regarding further and closer marriage preparation. Some changes were suggested, for the welfare of marriage.